Butane dehydrogenation on vanadium supported catalysts under oxygen free atmosphere - Volpe, María Alicia (2004)
The present study investigates the catalytic n-butane dehydrogenation under oxygen free atmosphere using VOx supported on USY, NaY, γ-Al2O3 and α-Al2O3. Experiments are developed at 520°C in a fixed bed microreactor. Catalyst characterization via TPR demonstrates the presence of different VOx species with the nature of these species being a function of the catalyst support. The acidic properties of the prepared catalysts are also evaluated using NH3 TPD with the following order of acidity being observed: VOX/γ-Al2O3 > VOxM/α- Al2O3 > VOx/USY. Reactivity experiments show that the VOx/USY provides both the highest catalytic activity and butane selectivity, with the VOx/γ-Al2O3 displaying a lower activity and butane selectivity and the other tested catalyst samples being essentially inactive. The superior performance of the VO x/USY catalyst is assigned to its mild acidity.